Analisis Kinerja Pelayanan Administrasi Kependudukan di Kantor Kecamatan Saparua Kabupaten Maluku Tengah - Winny Prajawati Salamor; Normawati; Hengky Virgo Richardo Pattimukay (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to analyze the performance of population administration services at the Saparua Subdistrict Office, Central Maluku Regency. The research focuses on four key indicators: productivity, service quality, responsiveness, and accountability of public service officials. A descriptive qualitative approach was employed, using in-depth interviews, direct observation, and documentation conducted between Juli–September 2024. The findings indicate that population administration services in Saparua still face several challenges, including limited human resources, inadequate facilities, and unstable internet connectivity. Service productivity remains suboptimal, with an average of 20–25 documents processed per day out of a target of 40. Service quality and responsiveness are constrained by weak public communication and insufficient supervision. Nevertheless, there is a growing commitment from local government to enhance service delivery through the digitalization of the Population Administration Information System (SIAK) and continuous capacity building for civil servants. The study concludes that improving service performance requires an integrated strategy encompassing digital infrastructure enhancement, human resource strengthening, and managerial reform oriented toward digital governance. The results are expected to contribute empirically to strengthening digital public service transformation policies in archipelagic regions.